DEVELOPMENT AND EVALUATION OF TOMATO POWDER IN CORPORATED RICE BASED COLD EXTRUDATES - JESSIE W SUNEETHA, RONANKI SRIVALLI, B. ANILA KUMARI, K. UMA MAHESWARI, B. NEERAJA PRABHAKAR & (The Journal of Research, PJTSAU, 2019)
Rice contains approximately 7.3% protein, 2.2% fat, 64.3% available carbohydrate, 0.8% fiber and 1.4% ash content (Zhou et al. 2002). Due to its hypoallergenic properties and absence of gliadin, rice is considered as good source for making gluten free food products. Rice flour has become an attractive ingredient in the extrusion industry due to its bland taste, attractive white colour, hypoallergenicity and ease of digestion (Kadan et al. 2003).